2021
DOI: 10.1186/s12877-021-02351-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic geriatric assessment for older patients with frailty in the emergency department: a randomised controlled trial

Abstract: Background Comprehensive geriatric assessment provided in hospital wards in frail patients admitted to hospital has been shown to reduce mortality and increase the likelihood of living at home later. Systematic geriatric assessment provided in emergency departments (ED) may be effective for reducing days in hospital and unnecessary hospital admissions, but this has not yet been proven in randomised trials. Methods We conducted a single-centre, rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Table 1 presents characteristics of the included studies. All studies were published in English and the primary author affiliation was mainly from North America [7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] (44%) and Europe [44][45][46][47][48][49][50][51][52][53][54][55] (35%). No papers had been published before 2015, and most of the papers (76%) were published beginning 2019.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents characteristics of the included studies. All studies were published in English and the primary author affiliation was mainly from North America [7,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] (44%) and Europe [44][45][46][47][48][49][50][51][52][53][54][55] (35%). No papers had been published before 2015, and most of the papers (76%) were published beginning 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were published in emergency medicine journals (41%) [7, 30, 32, 33, 36, 40, 46, 48-50, 53, 54, 56, 57], geriatric journals (38%) [31,34,35,38,39,41,42,45,47,56,58,59] or other types of journals (21%) [37,43,51,52,55,60,61]. Two-thirds of the studies were prospective cohorts [7, 30, 33, 35-38, 40, 42, 43, 47-50, 52, 54-59, 62], while the remaining were retrospective cohorts (24%) [34,39,41,45,46,53,60,61], intervention studies (9%) [31,44,51] or cross-sectional studies (3%) [32] (Table 1). One study [45] was performed in pre-hospital setting only, and another one [43] included both pre-hospital and ED patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane Library review from 2017 showed that a CGA carried out by a hospital for patients aged 65 and older does not affect mortality or i/p ADL capacity in the following year [26]. A recent RCT showed that systematic geriatric assessment for older (≥ 75 years) adults with frailty defined by CFS in the emergency department did not reduce hospital stay during one-year follow-up [27].…”
Section: Treatmentmentioning
confidence: 99%
“…Comprehensive geriatric assessment (CGA) has been identified as a potentially useful approach to this aim as it was shown effective to improve functional trajectories and the likelihood of remaining at home up to 12 months after discharge from dedicated geriatric wards [ 9 ];[ 18 , 19 ]. Indeed, several studies that specifically examined CGA-based geriatric consultations performed by teams working within EDs reported promising results in detecting vulnerability and preventing admission [ 20 22 ]. However, evidence from these studies was less clear about their effect on length of stay or 30-day readmission [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%